DESAIN IN SILICO DNA PROBE PENDETEKSI MUTASI DAERAH RESISTENSI QUINOLON Gen gyrA DAN gyrB Mycobacterium tuberculosis - Pramiswari, Tasya; Tamara, Jennifer; Febrianti, Ni Made; Chandra Yowani, Sagung (SIMBIOSIS, 2019)
Fluoroquinolone (FQ) is the main drug used in MDR-TB therapy resistance to FQ can cause death and increase the risk of treatment failure in MDR-TB patients. Mutations in gyr A gene and gyr B gene from Mycobacterium tuberculosis are responsible for the occurrence of FQ resistance. The highest mutation of gyr A gene in QRDR was found in codon 94, while mutations in gyr B gene was found in codon 500. M. Tuberculosis which resistant to FQ can be detected using the Real Time Polymerase Chain Reaction (RT-PCR) method with DNA probe.                                                                                                                                                                                                                             This study will design the nucleotide sequence of the TaqMan type probe using the Clone Manager Suite 9.2 program. The results of the DNA probe design were then analyzed in two stages, which is based on the probe criteria in general and based on the TaqMan probe labeling criteria. The design of the mutant probe DNA using the program produced 1 probe for Asp94Ala specific mutations in the gyr A gene and 33 probes for Asp500Ala specific mutations in the gyr B gene. After being analyzed by the two criteria, it was obtained the A94MA1 probe with the 5 '-TCGATCTACGCCAGCCTGGT-3' sequence and B500MA12 probe with the order of 5 '-TACCACAAGCTCGTGCTGATGGC-3'. The results of these probes meet both criteria and can be used to detect mutations in codon 94 gyr A genes and codons 500 gyr B genes of  Mycobacterium tuberculosis .